Pengaruh Keyakinan Islam dan Gender terhadap Ethical Judgment - Sari, Yesi Novita; Serly, Vanica (Universitas Negeri Padang, 2024)
This study aims to examine the influence of Islamic Belief and Gender on Ethical Judgment. It is a quantitative research with data obtained through questionnaires. The research population consists of Accounting students from the Faculty of Economics at Universitas Negeri Padang, Politeknik Negeri Padang, Universitas Putra Indonesia, Universitas Dharma Andalas, and Universitas Andalas, who have taken auditing courses and are Muslims from the 2019, 2020, and 2021 cohorts, totaling 1,727 students. The sample was selected using the Slovin formula, resulting in 328 students. The results of the study show that the Islamic Belief variable (X1) does not affect ethical judgment (Y), and the Gender variable (X2) also does not affect ethical judgment (Y). This study can contribute positively to the research subjects. It can help them avoid various ethical dilemmas they might face when entering the workforce. Additionally, it can provide educators with insights to better develop ethical and religious values.